Development and Validation of a Self-Quantification Scale for Patients With Hypertension - Ma, Guiyue; Zhong, Zhuqing; Duan, Yinglong; Shen, Zhiying; Qin, Ning; Hu, Dehua (Frontiers in Public Health, 2022)
Background: The self-management ability of patients with hypertension is poor, and self-quantification increases gradually with the development of electronic. Self-quantification for patients with hypertension has important implications for individual health. Methods: The instrument was developed based on protection motivation theory with literature review, qualitative interview and focus group discussions and pilot testing. A total of 360 patients with hypertension were investigated using the scale. The psychometric properties of the scale were evaluated with respect to validity and reliability employing internal consistency reliability, split-half reliability, test-retest reliability, content validity (S-CVI/Ave and I-CVI) and construct validity (exploratory factor analysis and confirmatory factor analysis). Results: The final scale had 30 items with seven sub-domains. The Cronbach's α for all domains was 0.900 with a range of 0.817-0.938. The split-half reliability coefficient for all domains was 0.743 with a range of 0.700-0.888. The test-retest reliability coefficient for all domains was 0.880 with a range of 0.849-0.943. The S-CVI/Ave for all domains was 0.922 with a range of 0.906- 0.950, and the I-CVI of each item was a range of 0.800-1.000. The result of confirmatory factor analysis of this scale showed that χ2/df was 2.499, RMSEA = 0.065, GFI=0.865, NFI=0.84, IFI=0.934, TLI=0.914, CFI=0.933, RFI=0.865. The Pearson’s coefficients between the total scale and its each domain were ranging from 0.347 to 0.695, and each domain ranged from 0.130 to 0.481. Conclusion: The scale proved has good validity, reliability and can be used as the self-quantification scale for patients with hypertension.